Improving the Quality of Education With School-Based Management: Challenges and Opportunities - Hartinah; Aura Wida Rofahima (Institut Agama Islam Negeri Sorong, 2024)
School-based management has emerged as a decentralized approach to improving the quality of education. This article explores the challenges and opportunities of implementing school-based management to enhance the quality of education. This research uses a literature review approach with data collection techniques through documentation studies, namely collecting, reading, noting, and processing relevant literature. The research findings identified vital challenges such as lack of understanding, limited resources, resistance to Change, and lack of community participation. However, school-based management also offers significant opportunities, such as program adjustments to local needs, innovative curriculum development, increased stakeholder engagement, more efficient resource management, and enhanced accountability and transparency. These findings are compared with previous research to provide new insights and a broader perspective. In conclusion, the effective implementation of school-based management requires comprehensive and sustainable efforts, including enhancing understanding, providing adequate resources, community involvement, and applying transparent and accountable management practices.